Formulasi Krim Ekstrak Daun Kersen (Muntingia calabura L.) dan Seng Oksida Sebagai Sediaan Tabir Surya - Rosyidi, Viddy Agustian; Ameliana, Lidya; maarif, safirul (Journal of Agropharmacy, 2025)
Sunscreen has two types of working mechanisms, namely chemical absorber and physical blocker. Sunscreens are usually made from synthetic chemicals, but currently there are many natural ingredients that have potential as sunscreens and are believed to have little negative effect compared to synthetic chemicals. One example of a natural ingredient that has potential as a sunscreen is kersen leaves. Kersen leaves contain quite a lot of flavonoid and polyphenol compounds, therefore cherry leaves have the potential to be an antioxidant and natural sunscreen. The effectiveness of cherry leaf sunscreen can be optimized by adding a physical blocker sunscreen ingredient, namely zinc oxide. Based on research results, the in vitro effectiveness value of sunscreen cream preparations provides the best results with an SPF value of 2.193 ± 0.152 which is included in the minimal protection category with a reduction in the percentage transmission value of erythema (%TE) of 1.513 ± 0.523 which is included in the sunblock category. and the percent pigmentation transmission (%TP) value was 1,378 ± 0.325, which is included in the sunblock category.